1986
DOI: 10.1111/j.1365-2265.1986.tb01662.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Dose Ketoconazole Therapy on the Main Plasma Testicular and Adrenal Steroids in Previously Untreated Prostatic Cancer Patients

Abstract: In vitro, ketoconazole has been shown to block testicular and adrenal 17,20-lyase, which converts progestins to androgens. At higher concentrations, it also inhibits 11 beta-hydroxylase, 20,22-desmolase and 17 alpha-hydroxylase. To determine the differential hormonal effects of a 2-week ketoconazole high-dose therapy, the plasma levels of 10 major androgens, gluco- and mineralocorticoids were measured in 14 previously untreated patients with metastatic prostate cancer. Within 24 h, plasma testosterone fell fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 17 publications
1
40
0
Order By: Relevance
“…However, as ketoconazole has low specificity for CYP1A1, the dose required for inhibition of CYP17A1 could be associated with significant toxicity. Moreover, loss of CYP17 inhibition with an increase in circulating adrenal androgens often occurred at progression [9]. Abiraterone inhibited both 17α-hydroxylase and C17,20 lyase activities significantly more potently than ketoconazole.…”
Section: Rational Approach To the Development Of A Specific And Potenmentioning
confidence: 99%
“…However, as ketoconazole has low specificity for CYP1A1, the dose required for inhibition of CYP17A1 could be associated with significant toxicity. Moreover, loss of CYP17 inhibition with an increase in circulating adrenal androgens often occurred at progression [9]. Abiraterone inhibited both 17α-hydroxylase and C17,20 lyase activities significantly more potently than ketoconazole.…”
Section: Rational Approach To the Development Of A Specific And Potenmentioning
confidence: 99%
“…The effective inhibition of the 14a-demethylase enzyme (that is responsible for its antifungal properties) occurs at low doses of ketoconazole, whereas much higher doses are required for the non-specific inhibition of CYP17 (De Coster et al, 1986) and 11b-hydroxylase (Loose et al, 1983), but this results in neurological, respiratory and hepatic toxicities which are common and severe, with up to 20% of patients discontinuing treatment.…”
Section: Prior Experience With Ketoconazolementioning
confidence: 99%
“…The mammalian CYPs are also involved in the biosynthetic pathways of skin endobiotics such as leukotrienes and RA [3,[54][55][56], which may have implications in the development of certain skin disorders like psoriasis and atopic eczema [57], In view of the involvement of CYPs in leukotriene and RA metabolism, some azole derivatives (such as imidazole) have been shown to possess antipsoriatic ac tions [58], The imidazoles have been proved to be more successful in the treatment of some androgenic skin lesions such as hirsutism, alo pecia and acne [59][60][61], The retinoids have extensively been used for the treatment of a number of various acne types [62], Studies from our laboratory have also shown that sev eral CYP inhibitors such as synthetic flavones and plant phenols reduce the amount of carci nogenic compounds in skin by inhibiting the AHH activity which, in turn, decreases the binding of carcinogens to DNA [63], Other studies from our laboratory and elsewhere have also shown the therapeutic potential of ketoconazole, clotrimazole and liarozole against a number of dermatological lesions including tumors [64][65][66] …”
Section: Pharm Acological and Clinical Importance Of C Y P S For The mentioning
confidence: 99%